ESG and Corporate Valuation of Non-financial Listed Firms: Evidence from China (International Journal of Applied Research in Management and Economics, 2025)
ESG has become increasingly important for modern businesses seeking to drive growth while achieving sustainable development. Studies have found a significant positive relationship between a company's ESG performance and its market valuation, as measured by Tobin's Q. This paper evaluates the effect of ESG on the corporate valuation of Chinese non-financial listed firms during 2019 and 2024 by using multiple regression analysis and robust tests. The results indicate that corporate valuation is positively correlated with social factors, governance factors, and overall ESG score, while it is negatively correlated with environmental factors. This suggests firms should focus on enhancing their internal governance systems, including strengthening the board, ensuring transparency, and managing stakeholder relationships. Digitization can also improve ESG scores by reducing costs and improving communications. While environmental factors may initially reduce valuation, green marketing and promoting eco-friendly products can help offset this by attracting environmentally conscious consumers and investors.